Lava flow hazard map of Piton de la Fournaise volcano - M. O. Chevrel; M. Favalli; N. Villeneuve; N. Villeneuve; N. Villeneuve; A. J. L. Harris; A. Fornaciai; N. Richter; N. Richter; N. Richter; A. Derrien; A. Derrien; et al. (Natural Hazards and Earth System Sciences, 2021)
Piton de la Fournaise, situated on La Réunion island (France), is one of the most active hot spot basaltic shield volcanoes worldwide, experiencing at least two eruptions per year since the establishment of the volcanological observatory in 1979. Eruptions are typically fissure-fed and form extensive lava flow fields. About 95 % of some ∼ 250 historical events (since the first confidently dated eruption in 1708) have occurred inside an uninhabited horseshoe-shaped caldera (hereafter referred to as the Enclos), which is open to the ocean on its eastern side. Rarely (12 times since the 18th century), fissures have opened outside of the Enclos, where housing units, population centers, and infrastructure are at risk. In such a situation, lava flow hazard maps are a useful way of visualizing lava flow inundation probabilities over large areas. Here, we present the up-to-date lava flow hazard map for Piton de la Fournaise based on (i) vent distribution, (ii) lava flow recurrence times, (iii) statistics of lava flow lengths, and (iv) simulations of lava flow paths using the DOWNFLOW stochastic numerical model. The map of the entire volcano highlights the spatial distribution probability of future lava flow invasion for the medium to long term (years to decades). It shows that the most probable location for future lava flow is within the Enclos (where there are areas with up to 12 % probability), a location visited by more than 100 000 visitors every year. Outside of the Enclos, probabilities reach 0.5 % along the active rift zones. Although lava flow hazard occurrence in inhabited areas is deemed to be very low (< 0.1 %), it may be underestimated as our study is only based on post-18th century records and neglects older events. We also provide a series of lava flow hazard maps inside the Enclos, computed on a multi-temporal (i.e., regularly updated) topography. Although hazard distribution remains broadly the same over time, some changes are noticed throughout the analyzed periods due to improved digital elevation model (DEM) resolution, the high frequency of eruptions that constantly modifies the topography, and the lava flow dimensional characteristics and paths. The lava flow hazard map for Piton de la Fournaise presented here is reliable and trustworthy for long-term hazard assessment and land use planning and management. Specific hazard maps for short-term hazard assessment (e.g., for responding to volcanic crises) or considering the cycles of activity at the volcano and different event scenarios (i.e., events fed by different combinations of temporally evolving superficial and deep sources) are required for further assessment of affected areas in the future – especially by atypical but potentially extremely hazardous large-volume eruptions. At such an active site, our method supports the need for regular updates of DEMs and associated lava flow hazard maps if we are to be effective in keeping up to date with mitigation of the associated risks.